Digital technology and outdoor experiential learning. Issue 2 (2nd April 2020) - Hills, David; Thomas, Glyn
ABSTRACT: Any use or non-use of digital technology in outdoor experiential learning requires critical examination. Digital technology can undermine the aim of being outdoors, but it can also create opportunities to enhance outdoor learning experiences. This paper presents a conceptual framework, based on a systematic review of the literature, that facilitators can use to think critically about their use (or non-use), of digital technology in outdoor experiential learning. The three key parts of the framework are pedagogical considerations, affordances of digital technology and consequences of decisions. The framework is designed to help facilitators of outdoor experiential learning make informed decisions or retrospectively review the decisions they made about the use (or non-use) of digital technology. The strength of the framework is that it encourages facilitators to engage in the critical evaluation of the intended and unintended consequences of digital technology use (or non-use) in outdoor experiential learning.